Data Leakage Prevention system : protection of classified information in Chief Government Security Office - Syarifuddin Bin Palawa (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2017)
Data Leakage Prevention (DLP) system is used in Chief Government Security Office (CGSO) to protect classified information in the organization. This study aims to investigate the effectiveness of DLP system by analyzing the relationship between the effectiveness and the challenges towards the system acceptance. It also examines the acceptance of the DLP system implementation based on end users' perception. Malaysian public sectors had formulated comprehensive policies and regulations in managing government's official information to protect the facilities of Information and Communication Technology (ICT). However due to the rapid development of ICT, there are still loopholes that needed to be improved, in particular data protection in ICT. A survey questionnaire was conducted on sixty (60) respondents to gain feedback from the end users of the DLP system in CGSO. The main finding shows that the implementation of the DLP system in CGSO was able to increase the level of protection of classified information. It was also found that there was a significant correlation between the effectiveness and acceptance; and correlation between the users acceptance and the challenges faced by them. This study can be used to help CGSO in making decisions for the continuation of the implementation of the DLP system and can be used as a reference in future studies.